2010
DOI: 10.1111/j.1551-2916.2010.03931.x
|View full text |Cite
|
Sign up to set email alerts
|

Densification and Mechanical Properties of Spark Plasma Sintered B4C with Si as a Sintering Aid

Abstract: B4C ceramics doped with different Si contents were fabricated by the spark plasma sintering technique. Pure B4C ceramic could be densified to 99% of the theoretical density. The sinterability could be further improved by the addition of a small amount of Si due to the formation of liquid Si during sintering. The incorporation of Si could also remarkably increase the mechanical properties of B4C ceramics. The Vickers hardness, flexural strength, and fracture toughness of the sample with 8 wt% Si could reach 41.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…It can be seen that all composites could be densified to around 99% of their theory densities after SPS at 1800°C, demonstrating that SPS is a very effective technique to promote the densification of B 4 C ceramics. The sintering temperature for fully dense GNP/B 4 C composites is in good consistence with the sintering temperature for SPSed B 4 C ceramics reported in literature [17,18] and much lower than that of hot-press sintering [19]. Due to the relatively low GNPs concentration, the sinterability of B 4 C was almost not influenced by the addition of GNPs.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 67%
“…It can be seen that all composites could be densified to around 99% of their theory densities after SPS at 1800°C, demonstrating that SPS is a very effective technique to promote the densification of B 4 C ceramics. The sintering temperature for fully dense GNP/B 4 C composites is in good consistence with the sintering temperature for SPSed B 4 C ceramics reported in literature [17,18] and much lower than that of hot-press sintering [19]. Due to the relatively low GNPs concentration, the sinterability of B 4 C was almost not influenced by the addition of GNPs.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 67%
“…Because of the rapid heating, some Si can not react with graphite before they melt. The molten Si could increase the transport rate of materials and thereby enhance the sintering rate [24]. ZrC-SiC is sintered to dense fast at relatively low temperature [25].…”
Section: Methodsmentioning
confidence: 99%
“…The highest relative density of 99.84 7 0.07% was acquired with 10 wt% Si addition. Ye et al [11] reported that the shrinkage rate of the Si-doped B 4 C specimens starts at 1310-1360 1C and completes before 1800 1C. Furthermore, they suggested that the improvement in sinterability of Si doped B 4 C was attributed to the formation of liquid Si which further reacted with B 4 C to form SiC during sintering.…”
Section: Resultsmentioning
confidence: 95%
“…3. Ye et al [11] suggested that the reduction in B 4 C grains by using Si additive was attributed to the formation of SiC phase which can pin migrating grain boundaries and thus restraining the growth of B 4 C grains. The effect of Si addition on the Vickers hardness and flexural strength of B 4 C is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%